Incidence rate and spatio-temporal clustering of type 1 diabetes in Santiago, Chile, from 1997 to 1998 Taxa de incidência e agrupamento espaço-temporal de diabetes tipo 1 em Santiago, Chile, de 1997 a 1998 - JL Santos; E Carrasco; AL Moore; F Pérez-Bravo; C Albala (Universidade de São Paulo, 2001)
OBJECTIVE: To estimate the incidence rate of type 1 diabetes in the urban area of Santiago, Chile, from March 21, 1997 to March 20, 1998, and to assess the spatio-temporal clustering of cases during that period. METHODS: All sixty-one incident cases were located temporally (day of diagnosis) and spatially (place of residence) in the area of study. Knox's method was used to assess spatio-temporal clustering of incident cases. RESULTS: The overall incidence rate of type 1 diabetes was 4.11 cases per 100,000 children aged less than 15 years per year (95% confidence interval: 3.06--5.14). The incidence rate seems to have increased since the last estimate of the incidence calculated for the years 1986--1992 in the metropolitan region of Santiago. Different combinations of space-time intervals have been evaluated to assess spatio-temporal clustering. The smallest p-value was found for the combination of critical distances of 750 meters and 60 days (uncorrected p-value = 0.048). CONCLUSIONS: Although these are preliminary results regarding space-time clustering in Santiago, exploratory analysis of the data method would suggest a possible aggregation of incident cases in space-time coordinates. OBJETIVO: Estimar a taxa de incidência de diabetes tipo 1 na área urbana de Santiago, Chile, entre os dias 21 de março de 1997 e 20 de março 1998, assim como a avaliação do agrupamento espaço-temporal dos casos incidentes no período. MÉTODOS: Foram localizados 61 casos incidentes no tempo (dia do diagnóstico) e no espaço (lugar de residência) na área do estudo. O método de Knox foi usado para avaliar o agrupamento dos casos no espaço e no tempo. RESULTADOS: A taxa de diabetes tipo 1 foi estimada em 4,11 casos por 100.000 menores de 15 anos por ano (Intervalo de confiança 95%: 3,06 -- 5,14). Essa taxa de incidência parece ter aumentado desde a última estimativa realizada na região metropolitana de Santiago, nos anos 1986-1992. Foram construídas diferentes combinações de intervalos de espaço e tempo para determinar a agregação espaço-temporal dos casos incidentes. A quase significativa agregação de casos foi detectada usando as distâncias críticas de 750 m e 60 dias (valor p não corrigido = 0,048). CONCLUSÕES: Embora o estudo só mostre resultados preliminares do agrupamento espaço-temporal dos casos de diabetes tipo 1, em Santiago, a análise dos dados sugere uma possível agregação de casos incidentes nas coordenadas de espaço e tempo.